Problematic internet use associated with dry eye disease in medical students from Peru - Condori Meza, Ismael Benjamin (2021)
Purpose: Dry eye disease (DED) is a pathology of the ocular surface that is characterized by low tear production, which is widely associated with alterations in mental health. Problematic Internet use is defined as the feeling of concern about using this tool irresistibly, for longer periods than usual, accompanied by anguish that results from not doing so without reaching mania or hypomania behaviors. However, there are no published studies that report its relationship with problematic internet use (PIU). Therefore, this study aims to determine the association between PIU and DED in Peruvian medical students. Patients and methods: Analytical cross-sectional study that included human medicine students from Peru. For the measurement of main variables, the Ocular Surface Disease Index (OSDI) and the Internet Addiction Test (IAT) were used. To study their relationship, the Poisson regression analysis was used, we consider a p-value <0.05 as significant. Results: Data from 844 medical students were analyzed, 35.7% male and 64.3% female, with an average age of 21.8 ± 3.3 years. Likewise, the prevalence of DED was 70.9%, and the internet’s controlled use was 85.3%. In the analysis adjusted for DED, the men showed significant differences in the controlled use of the internet (p <0.003), of which those who had PIU, 50% had severe DED, as well as 80% of those addicted to the internet. The adjusted model showed that the PIU increases the prevalence of DED in men (PR = 1.17, 95% CI: 1.06 - 1.29), however, in women, no association was found between both variables.